SOME FEATURES OF THE HISTORY OF FLORA FORMATION IN THE CHU RIVER VALLEY (Experimental biology, 2022)
The article describes the history of the formation of vegetation and flora of the Chu river valley, its floristic composition and structure by geological periods. According to the results of many years of floristic research, today on the territory of the Chu River valley within Kazakhstan, there are 730 species of vascular plants belonging to 350 genera and 70 families. According to the species composition, the division Magnoliophyta dominates in the studied territory of the Chu River valley, which accounts for 99.3% and 17.6% belongs to Liliophyta. The largest number of species is concentrated in the subclasses Rosidae, Caryophyllidae, Lamiidae, Dilieniidae and Ranunculidae, each of which has families of 1-2 families, abundant genera and species, the rest of the families are represented by a small number. The history of the development of vegetation and flora of the river valley. Chu is only a part of the history of vegetation in Central Asia and Kazakhstan as a single region of major rank. Analysis of paleobotanical spore-pollen spectra of Tertiary and Quaternary deposits showed that the most ancient types of vegetation in the Chu River valley are xerophytic steppe and desert vegetation...
Keywords: Keywords: biodiversity, flora, vegetation, valley, Chu river.